STRATEGI PENGELOLAAN USAHA DALAM MENINGKATKAN DAYA SAING PADA UMKM KERIPIK SINGKONG MEKAR SARI MUARA TEWEH KABUPATEN BARITO UTARA - Fie; Monika (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2026)
The purpose of this study was to determine the business management strategies applied, the level of business competitiveness, and the appropriate management strategies to improve competitiveness at the Mekar Sari Cassava Chip MSME in Muara Teweh, North Barito Regency. This study used a qualitative approach with a descriptive research type. The informants in this study consisted of six people, including the business owner, employees, and consumers. Data were collected through interviews, observations, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the business management strategy at Mekar Sari Cassava Chip MSME has implemented management functions consisting of planning, organizing, implementing, and controlling, although they are still carried out in a simple and less structured manner. The level of competitiveness is considered fairly good, as seen from product quality, competitive pricing, customer service, marketing reach, and customer loyalty. Appropriate strategies to improve competitiveness include strengthening business planning, increasing product innovation, expanding marketing—especially through digital media—and conducting regular business evaluations.